The Music-Visual Synchrony in the TV Trailers - Galeano Galea, Pedro (Área Abierta. Revista de comunicación audiovisual y publicitaria, 2019)
The close relationship between music and image has great relevance in the effectiveness of the advertising message. This link is reinforced by music-visual sync, which is becoming more and more present in audiovisual advertising formats. This study aims to analyze this phenomenon applied to television trailers, by conducting a content analysis of more than one hundred trailers. The objectives of this research are: to point out the elements of the sound used, to know the representativeness of music-visual sync in television trailers and to know what types of synchrony are the most called upon. Despite the fact that the most used elements of sound are the voice and the silence, the music-visual sync is present in most of the analyzed cases. This synchrony is originated mainly by the rhythm of the assembly, and according to the indicated typologies they emphasize cases with a semi-hard and aesthetic music-visual sync.
Keywords: advertising; cinema; TV trailer; music; music-visual sync.